Current status and advances in ram semen cryopreservation - NTEMKA, A.; TSAKMAKIDIS, I. A.; KIOSSIS, E.; MILOVANOVIĆ, A.; BOSCOS, C. M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Ram semen cryopreservation contributes to genetic improvement through artificial insemination, eliminates geographical barriers in artificial insemination application and supports the preservation of endangered breeds thus the conservation of biodiversity. Sperm freezing process induces ultrastructural, biochemical and functional changes of spermatozoa. Especially, spermatozoa’s membranes and chromatin can be damaged, sperm membranes’ permeability is increased, hyper oxidation and formation of reactive oxygen species takes place, affecting fertilizing ability and subsequent early embryonic development. Aiming to improve ram frozen-thawed semen’s fertilizing capacity, many scientific investigations took place. Among them the composition of semen extenders, was a main point of interest. Semen preservation extenders regulate and support an environment of adequate pH and buffering capacity to protect spermatozoa from osmotic and cryogenic stress. Therefore, permeating (glycerol, dimethyl sulfoxide) and non-permeat ing (egg yolk, skimmed milk) cryoprotectants, sugars (glucose, lactose, trehalose, raffinose), salts (sodium citrate, citric acid) and antioxidants (amino acids, vitamins, enzymes) have been added and tested. Moreover, semen dilution rate, storage temperature, cooling rate and thawing protocol, are also some key factors that have been studied. The research results of this scientific topic are encouraging, not only about the freezing and thawing procedures, but also about the improvement of the additives’ properties. However, further research is needed to enhance the fertilizing ability of ram frozen-thawed semen, making its use practical in sheep reproductive management by the application of cervical artificial insemination.